A Promise of Unconditional Acceptance: Conversion to Christianity and the struggle for being in Sinja, Nepal - Samuele Poletti (European Bulletin of Himalayan Research)
Over the last few decades, Nepal’s Christian population has flourished even in quite remote contexts such as the Sinja Valley, in the north-western district of Jumla. The reasons why people are drawn towards Evangelical Christianity in particular are primarily existential and are intimately related to the problematic situations they are confronted with in their lives, which are rooted in turn in a very specific understanding of personhood. Among local Hindus, the lack of a unitary principle comparable to the Christian soul has important consequences. Far from being a permanent achievement, personhood needs to be constantly actualised in relational interaction with other people, through appropriate actions that match one’s social persona. This can cause a lot of tension, particularly when what happens in someone’s life hinders the fulfilment of social expectations. What seems to make Christianity appealing in Sinja is that, in this religion, one’s self is given a priori by God, thereby ensuring that everyone is of equal worth within the congregation. This promise of unconditional acceptance fosters a state of rediscovered existential peacefulness that many converts describe as the key outcome of their radical choice – a choice that is often facilitated by the occurrence of miracles. At the same time, conversion to Pentecostal Christianity also introduces unprecedented challenges, preventing us from viewing conversion as a simplistic, one-dimensional transition.